Effect on crystalline structure of AISI M2 steel using tungsten–thorium electrode through MRR, EWR, and surface finish. (August 2016) - Mandaloi, Gangaram; Singh, Subhash; Kumar, Pradeep; Pal, Kaushik
Graphical abstract: Based on the XRD results it has been found that the crystallographic structure of the composites has totally changed. In the un-machined surface it has been found that peaks are so sharp and intensity is too high. But as the current is increasing the peaks are broadened so that the crystallographic structure inside the material is changing and it is going to exfoliation stage which means the composites properties is increasing due to the homogeneous dispersion of the particles inside the matrix. Highlights: EDM technique has been used to study the effect on crystalline structure of the materials by the tool. MRR, EWR and SR of the workpiece and tool material have been measured. OSP, AFM and XRD were used to study about the crystallographic structure of the machined surfaces. Maximum and minimum value of MRR is obtained as 0.018876 mg/min and 0.001208 mg/min, respectively. Minimum and maximum value of EWR is obtained as 0.013986 mg/min and 0.250450 mg/min, respectively. Abstract: To investigate on the crystalline structure of AISI M2 steel by using tungsten–thorium electrode in electrical discharge machining (EDM) process was studied. Furthermore, the investigation were carried out for finding the value of material removal rate (MRR), electrode wear rate (EWR) and surface roughness (SR) of tool steel material depending upon three variable input process parameters. On the basis of weight loss, the value of MRR and EWR were calculated at optimized process parameter. Subsequently, surface topography of the processed material were examined through different characterization techniques like scanning electron microscopy (SEM), Optical surface profiler (OSP) and Atomic force microscopy (AFM), respectively. In XRD study, broadening of the peak was observed which confirmed the change in material properties due to the homogeneous dispersion of the particles inside the matrix. Lowest surface roughness and MRR of 0.001208 mg/min was obtained. Minimum surface roughness was obtained 1.12 μm and 2.18427 nm by OSP and AFM study, respectively. Also, minimum EWR was found as 0.013986 mg/min.